2020
DOI: 10.1177/1747954120938984
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the video assistant referee on the Chinese Super League

Abstract: With the development and advancement of technology, various types of high-tech auxiliary equipment have been gradually introduced into football matches to assist referees to officiate the game. The Chinese football Super League (CSL) introduced the video assistant referee (VAR) in the 2018 season. The purpose of this study is to explore the impact of the introduction of VAR on football matches and on referees’ performance. This study compared the data of all 240 games without VAR in the season 2017 and all 240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 31 publications
(35 reference statements)
7
53
3
2
Order By: Relevance
“…These results are similar to those provided by Han et al. 11 in the Chinese Super League. However, Lago-Peñas et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to those provided by Han et al. 11 in the Chinese Super League. However, Lago-Peñas et al.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Han et al. 11 found in the Chinese Super League that after the introduction of VAR there was a significant increase in the playing time of both the first half and second half, as well as for the whole match. They also found that the number of offsides and fouls dropped significantly.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Studies on match analysis in the Chinese Football Super League (CSL) have received considerable attention starting a few years ago because of its fast progress. These research studies focus primarily on key performance indicators (Mao et al, 2016;Yang et al, 2018;Gai et al, 2019), the impact of situational variables (Liu et al, 2019b), the evaluation of performance (Zhou et al, 2018(Zhou et al, , 2020, and the application of new technologies (Han et al, 2020) and complex networks (Yu et al, 2020;Zhao and Zhang, 2020). However, very few researches on the influence of key match events on CSL matches currently exist.…”
Section: Introductionmentioning
confidence: 99%
“…The only two quantitative studies investigating the VAR focused on its potential impact on various on-field events in different leagues, namely the German Bundesliga, the Italian Serie A, and the Chinese Super League [6,7]. In both studies, the authors found that the number of offside calls, fouls and yellow cards decreased significantly and that, not related to specific events, the overall duration of games increased slightly.…”
Section: Introductionmentioning
confidence: 99%